2021
DOI: 10.1073/pnas.2014043118
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-restricted control of established central nervous system autoimmunity by TNF receptor 2–expressing Treg cells

Abstract: CD4+Foxp3+ regulatory T (Treg) cells are central modulators of autoimmune diseases. However, the timing and location of Treg cell–mediated suppression of tissue-specific autoimmunity remain undefined. Here, we addressed these questions by investigating the role of tumor necrosis factor (TNF) receptor 2 (TNFR2) signaling in Treg cells during experimental autoimmune encephalomyelitis (EAE), a model of multiple sclerosis. We found that TNFR2-expressing Treg cells were critical to suppress EAE at peak disease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 45 publications
2
43
0
1
Order By: Relevance
“…The ability of Tregs to respond and dampen inflammation is essential for the resolution of immune responses and restoring normal immune homeostasis. Results from this study are consistent with reports in mice on the important function of TNFa-TNFR2 axis in Treg function at site of inflammation in models of colitis, GVHD and EAE (10,(32)(33)(34)36). We further show that human Tregs engage this pathway even in the absence of exogenously provided TNFa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ability of Tregs to respond and dampen inflammation is essential for the resolution of immune responses and restoring normal immune homeostasis. Results from this study are consistent with reports in mice on the important function of TNFa-TNFR2 axis in Treg function at site of inflammation in models of colitis, GVHD and EAE (10,(32)(33)(34)36). We further show that human Tregs engage this pathway even in the absence of exogenously provided TNFa.…”
Section: Discussionsupporting
confidence: 92%
“…In mouse models of type 1 diabetes, Tregs isolated from inflamed islets, but not those from lymphoid organs, are able to suppress anti-islet autoimmune attacks (9). Similarly, in a mouse model of multiple sclerosis, Tregs in the central nervous system (CNS) are critical for limiting pathology at the peak of disease and this tissue-restricted function of Tregs depends on TNF receptor 2 (TNFR2) signaling (10). In a mouse model of islet transplant, it was reported that Tregs first traffic to the inflamed graft to suppress alloimmune responses and subsequently retreat to draining lymph nodes to maintain tolerance (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of selective inhibition of TNF-R2 with a soluble TNF-R2 fusion protein (etanercept) has also been associated with the manifestation of MS-like demyelinating lesions due to the blockade of both sTNF and mTNF, confirming the idea that mTNF probably has a dominant role in the regenerative process and resolution of inflammation [ 33 ]. It has been recently suggested that the protective function in inflamed central nervous system pathology by T regulatory cells requires the surface expression of TNF-R2, therefore explaining the potential of some adverse effects of anti-TNF therapy in patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was due to constitutive expression of BLIMP1 in a STAT1-dependent manner, which antagonized IL-6-directed methylation of key regulatory regions of the Foxp3 locus. BLIMP1 expression, in turn, has been shown to be maintained by stimulation of the tumor necrosis factor receptor 2 (TNFR2), which is highly expressed in CNS Tregs ( Ronin et al, 2021 ). This is consistent with separate work demonstrating the importance of TNFRSF members at inducing and maintaining effector Tregs, in an NF-kB dependent manner ( Vasanthakumar et al, 2017 ).…”
Section: Tissue Tregsmentioning
confidence: 99%